IDENTIFICATION OF MORAL VALUES IN EARLY CHILDHOOD GAMELAN GAMES - Rumara, Puteri Aprilianeu Cahya; Maryatun, Ika Budi; Pamungkas, Joko; Cholimah, Nur (Universitas Gadjah Mada, 2024)
This research is specifically conducted to find out and focus on the identification of moral values contained in gamelan games at Budi Pekerti Kindergarten Sleman Yogyakarta. Researchers will use qualitative research with a descriptive approach in carrying out research in the field, exploring and processing data. Then the researcher obtained findings in the field which stated that there were several moral values such as character values that appeared in gamelan games at Budi Pekerti Kindergarten, including: sensitivity, harmony, self-adjustment, self-confidence, cooperation, socialization, being able to position themselves according to the demands of the times and perseverance. These values start from gamelan learning which is prepared through planning activities tailored to children's abilities, then implementing appropriate activities so that they can be realized and evaluations used in playing gamelan to see the development of successful behavior in the implementation of gamelan learning. Field results also show that activities/toys/learning carried out by carefully designing concepts will make it easier for teachers or coaches to achieve the expected goals, as well as gamelan games on children's character values at Budi Pekerti Kindergarten Sleman Yogyakarta.